Influence Business Principles, Organizational Culture, Fundamental Safe Work Practices, Operational Excellence Expectations, and Corporate Commitment to the Tenets of Corporate Operations and Corporate Performance Oil and Gas Chevron Indonesia - Sudarmo Sudarmo (Journal of Accounting, Business and Management (JABM), 2013)
The purpose this study is to explain that Influence Business Principle, Organizational Culture, Fundamental Safe Work Practices, Operational Excellence Expectations, and Corporate commitment to the tenets of corporate operations and corporate performance in oil and gas Chevron Indonesian Kalimantan, Sumatra, West Java, and Jakarta. Population research is employee of Chevron Indonesia amounted to 7000 people. Respondent sample are 225 persons. Statistical analysis used Structural Equation Models (SEM). The results showed that there are eleven (11) line direct relationship or indirectly. In this connection, there are four significant and positive. Six lines are not significant and positive path, and one Negative insignificant point. Four the significant points are: the business principle to influence of corporate operations tenets; Organizational culture to influence of corporate operations tenets; Workplace safety programs to influence of corporate operations tenets; and Expectations of the benefits of operating affect to corporate operations tenets. Six Positive insignificant are: Organizational culture affects corporate performance; Workplace safety programs affecting corporate performance; Expectations affect the performance benefits of corporate operations; Corporate commitment affect tenets of corporate operations; Corporate Commitment influence to corporate performance; and Tenets of corporate operations affect to corporate performance. One significant negative point is: business principles affect to corporate performance.